(untitled) (Journal of Scientific Research, 2014)
Three rapid, simple, inexpensive, precise, and accurate spectrophotometric procedures were developed for the determination of Perindopril erbumine (PPE) using cobalt-thiocyanate, citric acid and 2,3- dichloro-5,6-dicyano benzoquinone in bulk sample and in dosage forms. The procedures are based on the coordination complex of the drug (electron donor) and the chromogenic reagents used. The colored products are extracted into non aqueous solvents and measured spectrophotometrically at the optimum ?maxfor each complex. Regression analysis of Beer-Lambert plots showed good correlation in the concentration range of 30-70 µg mL?1, 4-20 µg mL?1 and 20-60 µg mL?1 for cobalt-thiocyanate, citric acid and 2,3- dichloro-5,6-dicyano benzoquinone, respectively. The apparent molar absorptivity, Sandells sensitivity, detection and quantification limits were calculated. The developed methods were successfully applied for the determination of PPE in bulk and pharmaceutical formulations without any interference from common excipients and hence can be used for their routine analysis. Keywords: Perindopril erbumine; Spectrophotometry; Cobalt-thiocyanate; Citricacid-acetic anhydride. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i2.16106 J. Sci. Res. 6 (2), 319-327 (2014)